Cyber Clash - Qonita, Fidaul; Zaimi, Hamas Dzulfikar; Nurdin, Ali (Pioneer: Journal of Language and Literature, 2024)
The development of social media presents new challenges related to the dynamics of digital communication, one of which is the cyber clashes between influencers and netizens on the TikTok platform. This phenomenon can be seen in the increase in violence on social media, one of which is verbal violence, such as abusive comments, threats, or insults to hate speech. Researchers conducted interviews with four influencers aged 19-26 years who have experienced violence on social TikTok. In addition, researchers also interviewed five netizens who are active on TikTok. Researchers want to examine the cyber clash between influencers and netizens more deeply in the context of verbal violence. Using descriptive qualitative research methods and interview approaches, researchers want to reveal the factors that drive cyber clashes and the impacts on the parties involved. The results showed that verbal violence occurs because there are differences in views, cancel culture and hyper-reactivity, as well as anonymity and impurity, and with that, the results showed. All informants received indirect types of verbal violence through their social media in the form of ridicule, body shaming, and bullying. This research is expected to provide recommendations to reduce verbal violence in the digital space and promote ethics.